2021
DOI: 10.3390/ijerph182011001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Reinfection Is a New Challenge for the Effectiveness of Global Vaccination Campaign: A Systematic Review of Cases Reported in Literature

Abstract: Reinfection with SARS-CoV-2 seems to be a rare phenomenon. The objective of this study is to carry out a systematic search of literature on the SARS-CoV-2 reinfection in order to understand the success of the global vaccine campaigns. A systematic search was performed. Inclusion criteria included a positive RT-PCR test of more than 90 days after the initial test and the confirmed recovery or a positive RT-PCR test of more than 45 days after the initial test that is accompanied by compatible symptoms or epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 208 publications
(152 reference statements)
1
10
0
1
Order By: Relevance
“…The ANOVA results underscored the importance of relapses that emerged, with a small effect size. At first, SARS-CoV-2 was expected to induce a monophasic disease; however, the increasingly common cases of clinical recurrence of COVID-19 symptoms [ 60 , 61 , 62 ] have led to an investigation into whether all suspected COVID-19 relapses are due to a prolonged positive status or reinfection with a new strain [ 63 , 64 , 65 ]. Studies have indicated that clinical relapse could be due to a low level of neutralizing antibodies [ 66 ], whereas others have hypothesized that disease recurrence is due to an inflammatory syndrome because of an inappropriate immune response [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ANOVA results underscored the importance of relapses that emerged, with a small effect size. At first, SARS-CoV-2 was expected to induce a monophasic disease; however, the increasingly common cases of clinical recurrence of COVID-19 symptoms [ 60 , 61 , 62 ] have led to an investigation into whether all suspected COVID-19 relapses are due to a prolonged positive status or reinfection with a new strain [ 63 , 64 , 65 ]. Studies have indicated that clinical relapse could be due to a low level of neutralizing antibodies [ 66 ], whereas others have hypothesized that disease recurrence is due to an inflammatory syndrome because of an inappropriate immune response [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, beyond the durability of the 2-dose vaccine–induced immunity against breakthrough infections, the magnitude of the booster-recalled memory B and T cell immunities has become another point of consideration. The durability and magnitude issues are also applicable to natural infection, as there is reinfection with 0.7%–1.9% of cases occurring in individuals with documented prior infection ( 23 ). Moreover, the definition of “fully vaccinated” has been under discussion at the US CDC and FDA, with focus on the authorization for third and fourth booster vaccinations for certain populations, including those who are immunocompromised ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 Tinjauan sistematis yang dilakukan oleh Lo Muzio, dkk. 39 melaporkan adanya 260 kasus reinfeksi dengan 92 (35,3%) kasus reinfeksi menunjukkan gejala yang lebih berat dari infeksi pertama (asimtomatik menjadi simtomatik) dan kasus reinfeksi yang menyebabkan kematian sebanyak 14 kasus. Tinjauan tersebut menemukan kasus reinfeksi banyak terjadi pada pasien berusia 21-40 tahun (40%) dan 41-60 tahun (35%).…”
Section: Manifestasi Klinis Kasus Reinfeksi Covid-19unclassified